IS/IT investment and organisational performance in the financial services sector: a credit union case study - Maimbo, Hilangwa; Pervan, Graham (University of South Australia, 2003)
This article presents preliminary results of research into the relationship between IS/ITinvestment and organisational performance in the Financial Services Sector (FSS). Thisresults presented in this paper are from the first case in a series of six separate cases withinthe Australian FSS. Case study methodology was used to collect data (from interviews,documents and other sources) in a small sized Credit Union. Preliminary results obtainedthus far indicate support for components of the IS/IT investment model. In addition, resultssuggest the presence of a set of intermediary variables, namely operations, product deliveryand customer service, but more research is needed to further develop and refine the model. Itis hoped that this model will lead to a better understanding of the business value of IS/IT andthe effects of both management practice and Strategic Information Systems Planning on therelationship between IS/IT investment and organisational performance.